INTEGRASI TRUST DAN TECHNOLOGY ACCEPTANCE MODEL (TAM) DALAM INTENTION TO TRANSACT (Studi pada Konsumen Pengguna Tokopedia) - Budiyanto Budiyanto; Dewi Pangestuning Utami (SEGMEN Jurnal Manajemen dan Bisnis, 2021)
Increasing advanced technology makes online shopping continue to grow from time to time. An easy, simple way to shop, and even consumers can get cheaper prices compared to traditional shops, is indeed a choice for consumers. Very high internet speed also supports the rapid e-commerce business in Indonesia. The purposes of this study is 1) the effect of trust on perceived usefulness, 2) the effect of trust on perceived ease of use, 3) the effect of trust on perceived risk, 4) the effect of trust on intention to transact, 5) the effect of perceived usefulness on intention to transact, 6) the effect of perceived ease of use on the intention to transact and 7) the effect of perceived risk on the intention to transact.Population in this study is all consumers who use Tokopedia marketplace. The sample of this study amounted to 120 people. The sampling technique used in this research is purposive sampling. Testing the hypothesis used multiple linear regression. The results show that 1) trust has a significant positive effect on perceived usefulness, 2) trust has a significant positive effect on perceived ease of use, 3) trust has a significant negative effect on perceived risk, 4) trust has a significant positive effect on intention to transact, 5) perceived usefulness has a significant positive effect on intention to transact, 6) perceived ease of use has a significant positive effect on intention to transact, 7) perceived risk is significant negative on intention to transact.Keywords: trust, perceived usefulness, perceived ease of use, perceived risk, intention to transact, tokopedia